Evaluation of an experiment to increase availability of healthier snack foods in vending machines situated within English sports facilities - Charlotte EL Evans; Stuart Worth; Rachel White; Emma K Strachan (Cambridge University Press, 2023)
Abstract Objective: To evaluate the impact of increased availability of healthier options on purchasing of different types of vending snack products sold in English leisure (sports) centres. Design: An evaluation of an intervention using pre-post methods and interrupted time series analysis. Products within the vending machines were altered over three phases to increase the availability of healthier options, using agreed nutrition criteria - Government Buying Standards for Food and Catering Services (GBSF) for England - as a guide, as well as product availability. The primary outcome was the change in mean weekly purchased energy between the first and third phase. Secondary outcomes included changes by phase and by week in weekly number of purchases, fats, sugars and salt for all products combined and by individual product categories. Setting: Fifteen sports centres in the city of Leeds, West Yorkshire, UK. Participants: Snack products sold in eighteen vending machines. Results: Energy purchased reduced from baseline to phase 2, for all product categories combined, by 47·25 MJ (95 % CI (−61·22, −33·27)) per machine and by 279 kJ, (95 % CI (−325, −266)) per product unit. There were reductions in most nutrients purchased in all individual product categories except chocolate confectionery. Nutrients per product unit decreased for all product categories except saturated fat in chocolate confectionery. Minimal underlying trends in the baseline phase were identified, indicating changes in outcomes were likely to be due to the intervention. Conclusions: Introducing standards to increase availability of healthier snack products in vending machines is feasible without substantially affecting sales.